INOVASI PELAYANAN PUBLIK DALAM PERSPEKTIF BEST PRACTICE (PRAKTIK TERBAIK) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU - Pransiska, Else; Meilani, Nur Laila (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
DPMPTSP Pekanbaru city is an institution that is engaged in public services within the scope of administrative services namely licensing serving and non-licencing. the service organized by DPMPTSP Pekanbaru city has been awarded almost every year and has been awarded as a role model public service in 2017. So, the purpose of this research to analyze public service that become best practice in the Department of Investment and Integrated One Stop Service Pekanbaru.The research is using the concept of best practice quoting from Eko Prasojo (20014:4), which explains that there are 3 indicators namely Impact, Partnership, and Sustainability. This research uses qualitative research metdod with descriptive data analysis and data analysis technique using interactive model (interactively model) from Milles and Huberman (1984) cited in Sugiyono (2014). In collecting the data the researcher using interview technique, observation, and documentation. The results of this research, it can be seen that the implementation of public service best practice in DPMPTSP Pekanbaru City has explained various innovations in public services. There are four innovations namely. (1) innovation prevention corruption public service that can realize clean and transparent service. (2) Innovation of capacity building of the apparatus, this innovation can improve employee morale and discipline. (3) Commitment, in this case commitment in the implementation of public services, related to service mechanism, facilities and infrastructure, and facilities. (4) Innovation of service quality improvement, this innovation related to electronic mobile service system renewal, although the community has not much know about it technically the system is ready. Therefore, the importance of socialization and promotion of service systems to determine the level of understanding of the community. The innovations have been implemented can lead to a service that can contribute positively to the community so as to create a satisfactory service for the community.Key word: Innovation, Public Service, Best Practice, One Stop Service.